2022
DOI: 10.1021/acs.estlett.1c00877
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Polydimethylsiloxane-Based Passive Air Sampler to Assess Personal Exposure to SARS-CoV-2

Abstract: Exhaled respiratory droplets and aerosols can carry infectious viruses and are an important mode of transmission for COVID-19. Recent studies have been successful in detecting airborne SARS-CoV-2 RNA in indoor settings using active sampling methods. The cost, size, and maintenance of these samplers, however, limit their long-term monitoring ability in high-risk transmission areas. As an alternative, passive samplers can be small, lightweight, and inexpensive and do not require electrical power or maintenance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Passive samplers do not require any external power or an air mover and rely on gravity, diffusion, and/or electrostatic forces to collect airborne particles, including bioaerosols. Passive sampling devices based on these collection principles include spore traps (Durham, 1946;Serrano-Silva and Calderón-Ezquerro, 2018), dust collectors (Cox et al, 2017), agar settling plates (Andon, 2006), polydimethylsiloxane pads (Angel et al, 2022), and specially-arranged polarized ferroelectric polymer films (Therkorn et al, 2017a). In particular, electrostatic collection combined with gravitational particle deposition can allow for greater collection efficiency of bioaerosols compared to gravitational settling alone (Therkorn et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Passive samplers do not require any external power or an air mover and rely on gravity, diffusion, and/or electrostatic forces to collect airborne particles, including bioaerosols. Passive sampling devices based on these collection principles include spore traps (Durham, 1946;Serrano-Silva and Calderón-Ezquerro, 2018), dust collectors (Cox et al, 2017), agar settling plates (Andon, 2006), polydimethylsiloxane pads (Angel et al, 2022), and specially-arranged polarized ferroelectric polymer films (Therkorn et al, 2017a). In particular, electrostatic collection combined with gravitational particle deposition can allow for greater collection efficiency of bioaerosols compared to gravitational settling alone (Therkorn et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indoors suggested that foam accumulated a higher molecular weight fraction of polar substances, likely associated with particles, and visible inspection of PDMS foam deployed outdoors revealed particles after only 1 week (Figure S12). As it has been done for PDMS sheets, , the uptake rate of PDMS foam could be quantitatively calibrated to define the useful linear-uptake period for gaseous- and particulate-phase analytes. In future real-world applications, incorporating diffusive barriers into the deployment casings around PDMS could reduce variability between people or locations, but such barriers must be designed to minimally interfere with collection of the airborne fine particulate fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Existing strategies for collecting viruses and other pathogens from the air and concentrating them for downstream characterization can be divided into two broad classes, those relying on active air sampling and those relying on passive (diffusive) air sampling (Figure 2). [30,52,53] Both collection mechanisms have advantages and disadvantages to integrating them into wearable sensors for the detection of airborne pathogens. Recent studies have primarily relied on active air samplers to study the spread of airborne viruses such as SARS-CoV-2 and Influenza A, both in hospital and commercial settings.…”
Section: Aerosol Collectionmentioning
confidence: 99%
“…Unlike ac-tive air samplers, passive samplers do not require forced airflow and instead let aerosol particles settle and adsorb onto a collection substrate like polydimethylsiloxane (PDMS) or filter-paper under ambient air conditions. [52,53,60] The lack of a pumping unit tends to make passive air samplers simpler to use and operate than active samplers and they tend to be smaller. For example, setups as simple as electrostatic cloth attached to a folder and a small PDMS pad in a wearable clip have been used as passive air samplers.…”
Section: Passive Aerosol Samplingmentioning
confidence: 99%
See 1 more Smart Citation